ASSESSMENT OF ANXIETY LEVEL AMONG SENIOR SECONDARY SCHOOL CHEMISTRY STUDENTS IN KUDAN LOCAL GOVERNMENT OF KADUNA STATE, NORTHERN NIGERIA - SALISU, HAUWA USMAN; NURU, RAMATU ASABE (Sokoto Educational Review, 2023)
The quest for an anxious free approach towards the learning of Chemistry is of paramount importance among students in developing countries. This research was conducted to determine the causes and level of Chemistry anxiety among Secondary School Students in Kudan Local Government of Kaduna State, Northern Nigeria, using a survey design and simple random sampling. The instruments used for data collection were Chemistry Anxiety Scale (CAS) and Chemistry AnxietyQuestionnaire (CAQ). Pearson's Product Moment Co-efficient was used to determine the r = 0.79 using test re-test method for instrument I (CAQ) while Spearman brown was used to determine r = 0.76 using split half method for instrument II. Results obtained revealed that Chemistry anxiety exist among these students (mean=3.61). The results also indicated that there is no significant gender disparity on anxiety level among the Students (P = 0.49 ?0.05). This research therefore recommends that teachers should observe anxious students while teaching and use effective instructional strategies like ethno-chemistry to reduce anxiety levels of these students. By this way, a more effective learning environment can be created.